Lung inflammation perturbation by engineered nanoparticles - Zhou, Xiaofei; Jin, Weitao; Ma, Jingjun (Frontiers in Bioengineering and Biotechnology, 2023)
In recent years, the unique and diverse physicochemical properties of nanoparticles have brought about their wide use in many fields; however, it is necessary to better understand the possible human health risks caused by their release in the environment. Although the adverse health effects of nanoparticles have been proposed and are still being clarified, their effects on lung health have not been fully studied. In this review, we focus on the latest research progress on the pulmonary toxic effects of nanoparticles, and we summarized their disturbance of the pulmonary inflammatory response. First, the activation of lung inflammation by nanoparticles was reviewed. Second, we discussed how further exposure to nanoparticles aggravated the ongoing lung inflammation. Third, we summarized the inhibition of the ongoing lung inflammation by nanoparticles loaded with anti-inflammatory drugs. Forth, we introduced how the physicochemical properties of nanoparticles affect the related pulmonary inflammatory disturbance. Finally, we discussed the main gaps in current research and the challenges and countermeasures in future research.